Disorder is good for you: the influence of local disorder on strain localization and ductility of strain softening materials - Tuzes, Daniel; Ispanovity, Peter Dusan; Zaiser, Michael (International Journal of Fracture, 2017)
We formulate a generic concept model for the deformation of a locally disordered, macroscopically homogeneous material which undergoes irreversible strain softening during plastic deformation. We investigate the influence of the degree of microstructural heterogeneity and disorder on strain localization (formation of a macroscopic shear band) in such materials. It is shown that increased microstructural heterogeneity delays strain localization and leads to an increase of the plastic regime in the macroscopic stress-strain curves. The evolving strain localization patterns are characterized.
Keywords: Fracture; Microstructures; Inhomogeneous material; Numerical algorithms; Probability and statistics